Microstructures and martensitic transformation behavior of superelastic Ti-Ni-Ag scaffolds. (October 2016) - Li, Shuanglei; Kim, Eun-soo; Kim, Yeon-wook; Nam, Tae-hyun
Graphical abstract: Highlights: The B2-R-B19′ transformation occurred in 49Ti-50.3Ni-0.7Ag alloy fibers. Annealing treated alloy fibers showed superelastic recovery ratio of 93%. Ageing treated scaffold had an elastic modulus of 0.67 GPa. Ageing treated scaffold exhibited good superelasticity at human body temperature. Abstract: Ti-Ni-Ag scaffolds were prepared by sintering rapidly solidified alloy fibers. Microstructures and transformation behaviors of alloy fibers and scaffolds were investigated by means of electron probe micro-analyzer (EPMA), differential scanning calorimetry (DSC) and X-ray diffraction (XRD). The B2-R-B19′ transformation occurs in alloy fibers. The alloy fibers have good superelasticity with superelastic recovery ratio of 93% after annealing heat treatment. The as-sintered Ti-Ni-Ag scaffolds possess three-dimensional and interconnected pores and have the porosity level of 80%. The heat treated Ti-Ni-Ag scaffolds not only have an elastic modulus of 0.67 GPa, which match well with that of cancellous bone, but also show excellent superelasticity at human body temperature. In terms of the mechanical properties, the Ti-Ni-Ag scaffolds in this study can meet the main requirements of bone scaffold for the purpose of bone replacement applications.